Optimization of SLiMS (Senayan Library Management System) in Improving the Performance of Library Service in High School - Ahdi Topan Sofyan; Pandu Adi Cakranegara; Purwo Agus Sucipto; Amrul Natalsa S; Era Sari Munthe5 (INFOKUM, 2022)
This research was conducted to implement SLiMS (Senayan Library Management System) in school libraries, where SLiMS is capable of handling library administration tasks that were previously performed manually, including collection management, inventory, catalogs, circulation, published data, and member data, as well as the borrowing process and collection returns. This study included interviews, observation, and documentation for students and teachers to obtain data. The findings of this study indicate that SLiMS adds value to the library through speedier library administration and management, enhanced librarian service performance, and increased library visits to support students' reading interests. As a result of system functionality testing using blackbox testing on seven scenarios, all system features are valid and in agreement with user needs analysis, allowing library system automation to optimize library services